Default Risk of Advanced Economies: An Empirical Analysis of Credit Default Swaps during the Financial Crisis - Dieckmann, Stephan; Plank, Thomas (Review of Finance, 2012)
Prices observed in the European sovereign credit default swap (CDS) market have severely increased since the beginning of the financial crisis. We document that the state of a country’s financial system and, since the beginning of the crisis, also the state of the world financial system have strong explanatory power for the behavior of CDS spreads, and the magnitude of this impact depends on the importance of a country’s financial system pre-crisis. Furthermore, Economic and Monetary Union member countries exhibit higher sensitivities to the health of the financial system. Our results suggest the presence of a private-to-public risk transfer through which market participants incorporate their expectations about financial industry bailouts.